Band edge modulated polymer layer to decrease back electron transfer and increase efficiency in sensitized solar cells - Arulkashmir, Arulraj; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (Advanced Energy Materials, 2016)
Recombination of charges residing in the TiO2 and redox electrolyte is one of the factors affecting the efficiency of dye sensitized solar cells (DSSCs). To circumvent this recombination, inorganic oxide barrier layers and organic silanes have been coated on TiO2/dyes. Due to the insulating nature of these layers, the efficiency increase is not very impressive. Conducting polymers with different band edges are used to suppress the charge recombination. Amongst the four polymers that are used as barrier layers, a polymer with a highest occupied molecular orbital energy at -5.8 eV and lowest unoccupied molecular orbital at -3.1 eV is found to increase the electron life time at TiO2 and decrease the charge recombination. The electron life time is found to be 88 ms. In addition to the long electron life time, the recombination resistance of this polymer is also high (91 Omega). This resistance is 18% higher than that measured for DSSCs without polymer barrier layer. These factors impact the efficiency of DSSCs. DSSCs fabricated with this polymer as barrier layer exhibit an efficiency of 9.2%, which is 22% higher than that of DSSCs without polymer barrier layer.